Analisis Keputusan Fatwa Tempatan Sewaktu Pandemik Covid-19 Menurut Kerangka Al-Tarakhkus Fi Al-Fatwa - Mohd Hapiz Mahaiyadin; Azri Bhari; Mohd Dasuqkhi Mohd Sirajuddin (USIM Press, 2024)
Vol. 26 No. 2 (2021): Special Edition